Allocapnia tsalagi, sp. n. and notes on A. recta (Claassen) from the Cumberland Plateau region of northeastern Alabama, U.S.A. - Grubbs, Scott A. (Zootaxa, 2008)
A new species of eastern Nearctic snowfly, Allocapnia tsalagi, is described from Jackson Co., Alabama, U.S.A. The new species is distinguished from closely-related A. malverna and A. mohri by details of the epiproct. Additionally, the dorsal process of the 8 th abdominal tergite of morphologically-variable A. recta is illustrated from the Cumberland Plateau region of northeastern Alabama.